2004
DOI: 10.1093/aob/mch179
|View full text |Cite
|
Sign up to set email alerts
|

Response of Cassava Leaf Area Expansion to Water Deficit: Cell Proliferation, Cell Expansion and Delayed Development

Abstract: Although cell growth processes were sensitive to mild water deficit, they recovered to a large extent, and much of the reduction in leaf area was caused by developmental delay and a reduction in cell division in the youngest, meristematic leaves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
77
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 30 publications
11
77
0
4
Order By: Relevance
“…This time lag was possibly caused by the dryness of the upper layer of soil in which the cassava cuttings were developing roots, which later went down to much moister layers (Alves & Setter, 2004). On the other hand, the real-time response of the percentage of leaf-likely pixels to mean cassava leaf fresh weight ( Figure 5) again indicates the leaf-likeliness of the black pixels in the binarized target areas (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time lag was possibly caused by the dryness of the upper layer of soil in which the cassava cuttings were developing roots, which later went down to much moister layers (Alves & Setter, 2004). On the other hand, the real-time response of the percentage of leaf-likely pixels to mean cassava leaf fresh weight ( Figure 5) again indicates the leaf-likeliness of the black pixels in the binarized target areas (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The digital images were pasted into a single digital image, and the best R/G value for discriminating between the leaves and other objects was statistically determined. The discriminatory power was evaluated by determining the fitness of the increase in leaf-likely pixels to a sigmoidal curve as the typical pattern of increase in cassava leaf biomass (Alves & Setter, 2004). Also, the authors examined greenness per luminosity when luminosity was given as a measure of brightness.…”
Section: Introductionmentioning
confidence: 99%
“…However, water use efficiency was highest when less irrigation was applied. Poor performance of these growth parameters in elevated temperature may be due to enhanced leaf senescence and growth retardation (Rehman et al, 2009) during growth phase, while it was recorded that as water plays its substantial role in cell division and elongation, ultimately in growth so restricted cell division and expansion (Alves and Setter, 2004) and more rate of leaf senescence (Hafsi et al, 2000) was reported due to water stress ( Table 2). The significantly different periodic trend regarding LAI, LAD and CGR under temperature regimes and irrigation levels is also elaborated in pictorial representation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Detrimental effects of water stress on crops depend on the developmental stage, its duration as well as on crop genotype (Beltrano and Marta, 2008). Wheat is sensitive to water stress, which results in low photosynthesis because of less intercepted area due to restricted cell division and expansion (Alves and Setter, 2004), more leaf senescence, smaller grain size and reduction in grain growth duration (Hafsi et al, 2000). The productivity of wheat relays on yield related attributes and these parameters show positive response to irrigation (Jahfari, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Em condições de deficit de água no solo ou de alta demanda evaporativa da atmosfera, as plantas de mandioca apresentam controle estomático bastante eficiente (El-Sharkawy et al, 1989;Alves & Setter, 2000, 2004El-Sharkawy, 2007). Contudo, a redução da abertura estomática pode limitar a taxa de difusão de CO 2 para o interior da folha, com efeitos diretos sobre a fotossíntese e o crescimento (Alves, 2002;El-Sharkawy, 2007).…”
Section: Introductionunclassified